Quantitative morphology of fossil adephagan beetle larvae including a first record from the Jehol biota does not indicate major diversity losses over time - Haug, Joachim T.; Fu, Yanzhe; Müller, Patrick; Haug, Gideon T.; Haug, Carolin (Zootaxa, 2024)
Coleoptera is a hyper-diverse group of animals with about 400,000 formally described species. Also the morphological diversity of beetles is very high, not only in the adults, but also in the larvae. To understand the evolutionary origin of this enormous diversity, investigations of fossils are crucial, but especially for the larvae such fossil are still scarce. In this study, we present 15 new fossil larvae from different deposits of Cretaceous to Miocene age, which we interpret as larvae of the beetle ingroup Adephaga. Most of these are three-dimensionally preserved and either embedded in amber or silicified. One specimen is a compression fossil, which is very rare for beetle larvae, and represents the first report of an adephagan beetle larva from the Early Cretaceous Jehol biota of China. Of all previously known and new fossil adephagan larvae and of selected extant ones the shapes of the head capsules and mandibles were compared with quantitative morphology methods (elliptic Fourier analysis and principal component analysis). The shapes of the fossil larvae lie all within the morphospace of those of the extant larvae, which indicates that the highest diversity in this aspect is present in the modern fauna, hence no diversity loss occurred. Other lineages of Holometabola show similar patterns, with indications of larval diversifications already in the Cretaceous, further specialisation afterwards, and no major losses. This pattern may be a reason for the enormous species richness of certain holometabloan groups in the modern fauna.